THE Migraine with periocular neuropathic component: a Case Report - Kuhn, Leonardo José; De Lazari, Alan Henrique; Gonçalves, Christian; De Lazari, Kassia Beatriz Valério Saibert; Oliveira, Sara Pessoa de; Barboza, Bárbara Evelin Gonçalves (Headache Medicine, 2024)
RELATO DE CASO Migraine with periocular neuropathic component: A Case Report KUHN, Leonardo José1; DE LAZARI, Alan Henrique1; GONÇALVES, Christian1; DE LAZARI, Kassia Beatriz Valério Saibert1; IORA, Giovana1; OLIVEIRA, Sara Pessoa de2; BARBOZA, Barbara Evelin Gonçalves3 1 Acadêmicos do Curso de Medicina do Centro Universitário Integrado de Campo Mourão – PR 2 Médica, Neurologista, Mestre, Docente do Centro Universitário Integrado de Campo Mourão - PR 3 Médica, Oftalmologista, Docente do Centro Universitário Integrado de Campo Mourão - PR Contato com autor: KUHN, Leonardo José Email: Endereço: Introduction: Chronic migraine affects around 2% of the world's population, being more common in women and significantly impacting quality of life and being more disabling than episodic attacks, generating annual expenses exceeding 20 billion dollars. Objective: To present a case report of migraine with periocular neuropathic component. Case Report: Woman, 43 years old, has suffered from migraines since the age of 11, presenting with a hemicranial, pulsatile headache of moderate intensity, associated with photophobia and phonophobia. Attacks fonofobia, lasting 3 days, worsen with movement and occur twice a month. During attacks, use dipyrone or sumatriptan 50 mg. However, what bothers her most is nonspecific and continuous right eye pain, about three times a week. The identified triggers are lack of sleep, stress and sun exposure. Not related to the menstrual period. Personal history includes endometriosis, myopia, astigmatism, keratoconus spots and Wolff-Parkinson-White syndrome, underwent surgery in childhood to ablate an anomalous beam. Currently, he has been using gabapentin 300 mg/night for 4 months. She has already used riboflavin and topiramate without significant improvement or adverse effects. In the initial assessment, he reported non-refreshing sleep, anxiety, irritability and constipation, and normal BMI. Duloxetine 30 mg was prescribed in the morning and magnesium chelate 300 mg at night, and she was referred to an ophthalmologist who began fitting her with corrective lenses. After 30 days of treatment, he observed a good response with adaptation to the medication and improvement in sleep, with only 4 days of pain in the last month. Currently, he continues to use Velija 30 mg in the morning, gabapentin 300 mg in the evening and biomagnesium 300 mg in the evening. It was decided to maintain medications and joint monitoring with the ophthalmologist. Conclusion: The reduction in the frequency and intensity of migraine attacks, as well as the positive response to treatment, highlight the importance of a multidisciplinary and individualized approach in the management of this complex condition, where the correction of astigmatism was fundamental as a factor in improving the attacks, resulting in a significant improvement in the patient's quality of life. Keywords: Migraine with Aura; Migraine Disorders; Therapeutics.